Risk factors associated with malignancy and with triage to surgery in thyroid nodules classified as Bethesda category III (AUS/FLUS). Issue 1 (January 2016) - Kuru, B.; Atmaca, A.; Tarim, I.A.; Kefeli, M.; Topgul, K.; Yoruker, S.; Elmali, M.; Danaci, M.
Abstract: Background: Selection of nodules for surgery diagnosed as Bethesda category III [atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) category] is very important. We aimed at to define the predictive factors for malignancy and factors associated with triage to surgery. Methods: The records of all patients with nodules who underwent fine needle aspiration biopsy (FNAB) and classified by Bethesda reporting system as AUS/FLUS between 2011 and 2015 at our institution were reviewed. Univariate and multivariate analysis were performed to select independent factors associated with thyroid cancer and with triage to surgery. Using independent risk factors for malignancy predictive index categories were created. Results: Of the 485 patients who were classified as AUS/FLUS on initial FNAB, 153 underwent surgery with the associated malignancy rate of 22.8%. The malignancy rates for AUS/FLUS patients with and without repeat FNAB were 37.5% and 16.2%, respectively. Multivariate logistic regression analysis revealed that solid structure, microcalcification, hypoechogenicity, increased vascularization, and irregular margin were found to be significant and independent risk factors associated for malignancy, and solid structure, microcalcifications, increased nodule size (≥2 cm) and younger patient age (<65 years) were associated with triage to surgery. Conclusions: Our findings showed that using predictive factors for malignancy in AUS/FLUS category as risk indices, an important proportion of patients (35%) who had nodules without any risk factors could be spared unnecessary surgery. We suggest that predictive indices should be considered for selection of the patients to triage to surgery.